Islamic leadership in hospital-associated cluster of Covid-19 management - Zainulabid, Ummu Afeera; Abu Hasan, Muhammad Abdus-Syakur; Mohd Rus, Razman; Adnan, Mohd Syafwan; Kamarudin, Norhidayah; Saidin, Nur Amira; Bachok, Nur Farhana; Ahmad, Hajar Fauzan; Expert, Paul; Abdul Razak, Fatimah (2022)
Introduction The pillar of accountability embodies the notion of leadership, which is greatly emphasised in Islamic culture. 'Each of you is a guardian and is responsible for his subjects,' says the Prophet Mohammad in the Hadeeth (Saheeh al Bukhari: 212). Here we share our experience in managing hospital-associated cluster of Covid-19 at Sultan Ahmad Shah Medical Centre @ IIUM that was inspired by Islamic leadership principles.